NON-NATIVE ENGLISH SPEAKERS’ AWARENESS OF ASSIMILATION IMPLEMENTATION IN THEIR PRONUNCIATION PRACTICE - Reski Ramadhani (Universitas Widyatama, 2022)
This study is intended to discuss the phenomenon occurring in phonological regulation, mainly assimilation. The study attempts to analyze the manners and types of assimilation that occur in non-native English speakers? pronunciation practice and to know the awareness of the students in the implementation of assimilation. This is a case study that employed a qualitative method with a descriptive approach through interviews and observation. The participant of this study is nine students of the non-English study of Garut Technology of the institute. The participants are chosen by using the purposive sampling technique. In the process of collecting data, students are given the transcript of speeches to be pronounced and the words and phrases are classified based on the manners and types of assimilation. The study reveals that the manners and types of assimilation mostly appearing in speakers? pronunciation practice are coalescent assimilation and the rest are progressive, regressive, and full assimilations. It shows that most students of the non-English study of Garut Technology of Institute have not fully been aware of the implementation of assimilation in their pronunciation practice. The implication of this study is to explore the importance of assimilation to help student lighten their English pronunciation when they speak at a rapid speed.